PENERAPAN PEMBELAJARAN BERBASIS MASALAH PADA MATERI SUMBER DAYA ALAM UNTUK MENINGKATKAN LITERASI SAINS SISWA SD - Rizki, Nurul Fauziah; Gusrayani, Diah; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
The development of teh times requires human to be smart anda figure carefully in choosing the information increasingly easy to obtained. At the school is expected to bring up the learning process thet produces a pattern og thingking scientifically and rationally. Therefore, this research aims to know the influence of problem-based learning, literacy abilities against science students on the material resources of nature. Methods and subjects in this research method of experimental and pre-grade III SDN Karapyak 1. Results show that: (1) probelm-based learning can improve science literacy on the material recources of significant ways, (2) problem-based learning material on natural resources can improve science literacy on group of high, medium, low. (3) there is a difference of science literacy ability enhancement by using problem-based learning in students of higher group, medium, and low, (4) students with learning respong positively using model problem based learning.